The kinetics of effector binding to phosphofructokinase. The allosteric conformational transition induced by 1,N6-ethenoadenosine triphosphate. - Roberts, D (1979)
1. The fluorescent ATP analogue 1,N6-etheno-ATP is a good substrate and an efficient allosteric inhibitor of rabbit skeletal-muscle phosphofructokinase. 2. Fluorescence energy transfer occurs between bound 1,N6-etheno-ATP and phosphofructokinase. 1,N6-Etheno-ATP fluorescence is enhanced, intrinsic protein fluorescence is quenched, and the excitation spectrum of 1,N6-etheno-ATP fluorescence is characteristic of protein absorption. 3. The binding reaction of 1,N6-etheno-ATP observed by stopped-flow fluorimetry is biphasic. The fast phase results from binding to the catalytic site alone. The slow phase results from the allosteric transition of the R conformation into the T conformation induced by the binding of 1,N6-etheno-ATP to the regulatory site. 4. The fluorescence signal that allows the transition of the R conformation into the T conformation to be observed does not arise from 1,N6-etheno-ATP bound to the regulatory site. It arises instead from 1,N6-etheno-ATP bound to the catalytic site as a consequence of changes at the catalytic site caused by the transition of the R conformation into the T conformation. 5. In the presence of excess of Mg2+, the affinity of 1,N6-etheno-ATP for the regulatory site is very much greater in the T state than in the R state.